MARKET STUDY OF COMPOUND FERTILIZER-BASED MINERAL AT TEA PLANTATION IN BANDUNG REGENCY - Ridwan Saleh; Eko Pranoto; Jafril Jafril (Indonesian Mining Journal, 2015)
The study of this research is to identify the market possibility of compound mineral fertilizer in Bandung Regency. The methodology used is survey method by using analysis model of market measurements. From the analysis and discussion, it can be identified the estimate of substantial potential of fertilizer market on tea plantation in Bandung Regency of IDR 111,070,309,152 with minimum market is IDR 74,742,993,050 or 67.29% from the total potential of fertilizer market as market penetration index. Meanwhile, the remains of 32.71% is market sen- sitivity area towards fertilizer demand. The estimate of the fertilizer demand is IDR 50,391,725,914 or 67.42% to a minimum market or 45.37% to potential market, and the remains of 54.63% is the market development opportunities in the future. Meanwhile its fertilizer competitor’s are Urea, SP 36, KCL, Kieserite, NPK (sodium, phosphate and potassium), MOP (muriate of potash) and ZK (zheng and potassium). Based on the questionnaire results to 97 respondents about the characteristics and perceptions of fertilizer consumers, it is formulated mix marketing of product aspects such as the physical form of mineral fertilizers is granulees. There are 2 types of packaging, 25 kgs and 50 kgs, and its long shelf life is between 3-6 months. The selling price of end consumers is under IDR 5,000 with payment system can be used in credit. Meanwhile, promotion is carried out directly at the experimental garden, by conducting distribution through two channels, namely cooperatives and agents/ distributors. According to overall analysis results, it can be concluded that by reviewing market and competition aspects, research and development of manufacture technology of compound fertilizer-based mineral is reason- able to be continued to the next stage in the commercialization process of technology.